Patients with congenital hypothyroidism demonstrate different altered expression of plasma fibrinogen and haptoglobin polypeptide chains - Yong, P.H.; Junit, S.M.; Harun, F.; Hashim, Onn Haji (Elsevier, 2006)
Objectives: To compare the plasma protein profiles of treated and untreated congenital hypothyroidism (CH) patients with those of normal control infants. Design and methods: Plasma samples were subjected to two-dimensional gel electrophoresis and silver staining or lectin detection. Resolved protein spots were analyzed by using computerized densitometry software. Results: The significant enhanced expression of the fibrinogen gamma-chain and reduced expression of haptoglobin beta-chain were demonstrated in the profiles of untreated CH patients using both silver staining and lectin detection methods. Lectin detection resolved only a single cluster of the haptoglobin beta-chain for the untreated patients, in contrast to five isoform clusters detected in the controls' and treated CH patients' profiles. Conclusions: Plasma from untreated CH patients demonstrated different altered expression of fibrinogen and haptoglobin polypeptide chains, which was normalized when patients were treated. Our data also suggest differences in structures of the N-glycans of haptoglobin beta-chain of the untreated CH patients. (c) 2005 The Canadian Society of Clinical Chemists. All rights reserved.